If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -3y = -13 Solving 7x + -3y = -13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 7x + -3y + 3y = -13 + 3y Combine like terms: -3y + 3y = 0 7x + 0 = -13 + 3y 7x = -13 + 3y Divide each side by '7'. x = -1.857142857 + 0.4285714286y Simplifying x = -1.857142857 + 0.4285714286y
| ln0.8/2 | | 4(x+6)=7x+33 | | -8t+-9=-41 | | K=8x+28 | | 3/5=2/3n | | j-8=5 | | x^9*x^6*x^3= | | 4(x+4)+5x=-20 | | 7log(x+93)=14 | | 3(x+4)+5x=-29 | | 4x^3-400x^2-x+100=0 | | 8x-5x+3=1x-7+10 | | x-1.2=4.8 | | 1x+6y=150 | | 5k-6=4 | | 6x^2-11cx+3c^2=0 | | -3k=27 | | 3x-10+7-10=21 | | 12x^6-16x^4/4x^3 | | 2x-x=-27 | | 2x^4+13x^2=7 | | 3x-10+7=21 | | Log(x+14)15=1 | | 2/5*45 | | 12c+6c= | | (5x)/(16)*(y)/(20) | | 2x-1*2+1.2x=10 | | .8x+.8x=32 | | 10x+5=45x-27-60 | | d+2d+d-3=39 | | 2x-1*2+1.2=10 | | 5x/16*y/20 |